International consensus on quality standards for brain health-focused care in multiple sclerosis - Hobart, Jeremy; Bowen, Amy; Pepper, George; Crofts, Harriet; Eberhard, Lucy; Berger, Thomas; Boyko, Alexey; Boz, Cavit; Butzkueven, Helmut; Celius, Elisabeth Gulowsen; Drulovic, Jelena; Flores, José; et al. (Multiple sclerosis (Houndmills, Basingstoke, England), 2019)
BACKGROUND: Time matters in multiple sclerosis (MS). Irreversible neural damage and cell loss occur from disease onset. The MS community has endorsed a management strategy of prompt diagnosis, timely intervention and regular proactive monitoring of treatment effectiveness and disease activity to improve outcomes in people with MS. OBJECTIVES: We sought to develop internationally applicable quality standards for timely, brain health-focused MS care. METHODS: A panel of MS specialist neurologists participated in an iterative, online, modified Delphi process to define 'core', 'achievable' and 'aspirational' time frames reflecting minimum, good and high care standards, respectively. A multidisciplinary Reviewing Group (MS nurses, people with MS, allied healthcare professionals) provided insights ensuring recommendations reflected perspectives from multiple stakeholders. RESULTS: Twenty-one MS neurologists from 19 countries reached consensus on most core (25/27), achievable (25/27) and aspirational (22/27) time frames at the end of five rounds. Agreed standards cover six aspects of the care pathway: symptom onset, referral and diagnosis, treatment decisions, lifestyle, disease monitoring and managing new symptoms. CONCLUSION: These quality standards for core, achievable and aspirational care provide MS teams with a three-level framework for service evaluation, benchmarking and improvement. They have the potential to produce a profound change in the care of people with MS.
Keywords: Neurology; roztroušená skleróza; benchmarking; standards; Delphi technique; mozek; lidé; Brain; Multiple sclerosis; quality improvement; Humans; delfská metoda; neurologie; consensus; konsensus; Consensus; Delphi Technique; Multiple Sclerosis